The Influence of Brand Image and Price Perception on Purchasing Decisions for Lux Bath Soap Product in Surabaya City - Aisyah, Kharisma Nur; Aminah, Siti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The tight competition in the soap industry has caused Lux to experience a decline between 2020 and 2024 due to various factors. The purpose of this research is to examine the impact of Brand Image and Price Perception on consumers' choices when buying Lux brand soap products in Surabaya City. Employing a quantitative methodology, 110 participants were carefully chosen via a purposive sampling technique. The collected data underwent analysis using Structural Equation Modeling (SEM), specifically the Partial Least Square (PLS) approach. The study's outcomes demonstrate a notable positive effect of both Brand Image and Price Perception on the purchasing behavior for Lux soap products in Surabaya City.